Robotic versus laparoscopic approach to treat symptomatic achalasia: systematic review with meta-analysis. Issue 10 (5th July 2019) - Milone, M; Manigrasso, M; Vertaldi, S; Velotti, N; Aprea, G; Maione, F; Gennarelli, N; De Simone, G; De Conno, B; Pesce, M; Sarnelli, G; De Palma, G D
SUMMARY: Minimally invasive Heller myotomy is considered the gold standard surgical approach for symptomatic achalasia because it is a safe and effective procedure. Over the last years, several studies comparing the laparoscopic and robotic approach for Heller myotomy have been published. Although the robotic approach appears to have some advantages over standard laparoscopy, data on this topic are still controversial and no definite conclusions have been drawn. This metanalysis has been designed to systematically evaluate and compare the effectiveness and safety of the robot-assisted Heller myotomy as compared to the standard laparoscopic approach. According to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, a systematic search on both laparoscopic and robotic Heller myotomy was performed in all the major electronic databases (PubMed, Web of Science, Scopus, EMBASE), using the following search string: (achalasia OR Dor) AND robotic. Six articles were included in the final analysis. A metaregression analysis was performed to assess the possible effects of demographic variables (age, gender, body mass indes (BMI)) and previous abdominal surgery or endoscopic intervention on the analyzed outcomes. No statistical difference was observed in operative times (mean difference (MD) = 20.79, P = 0.19, 95% confidence interval (CI) −10.05, 51, 62), estimated blood loss (MD = −17.10, P = 0.13, 95% CI −40.48, 5.08), conversion rate to open surgery (risk difference (RD) = −0.01, P = 0.33, 95% CI −0.05, 0.02), length of hospital stay (MD = −0.73, P = 0.15, 95% CI −1.71, 0.25) and long-term recurrence (odds ratio (OR) = 0.59, P = 0.45, 95% CI 0.15, 2.33). On the contrary, the robotic approach was found to be associated with a significantly significant lower rate of intraoperative esophageal perforations (OR = 0.13, P < 0.001, 95% CI 0.04, 0.45). Our results suggest that the robotic approach is safer than the laparoscopic Heller myotomy, encouraging the use of robot-assisted surgery. However, our analysis is limited because of the exiguous number of comparative studies and because most of the included studies were statistically underpowered, given the small sample size. Moreover, a high degree of heterogeneity was observed in most of published studies. Taking in consideration the additional costs of robot-assisted procedures, larger Randomized Controlled Trials (RCTs) are advocated to confirm the safety and effectiveness of the robotic approach, and its advantages over standard laparoscopic surgery. In conclusion, well-designed prospective trials and RCTs with homogeneous parameters are needed to draw definitive conclusions about the best surgical approach to pursue in treating symptomatic achalasia.